Effects of early- and late-gestational maternal stress and synthetic glucocorticoid on development of the fetal hypothalamus–pituitary–adrenal axis in sheep. (January 2013) - Rakers, Florian; Frauendorf, Vilmar; Rupprecht, Sven; Schiffner, Rene; Bischoff, Sabine J.; Kiehntopf, Michael; Reinhold, Petra; Witte, Otto W.; Schubert, Harald; Schwab, Matthias
<x xml:space="preserve">Abstract</x> Prenatal maternal stress (PMS) programs dysregulation of the hypothalamus–pituitary–adrenal axis (HPAA) in postnatal life, though time periods vulnerable to PMS, are still unclear. We evaluated in pregnant sheep the effect of PMS during early gestation [30–100 days of gestation (dGA); term is 150 dGA] or late gestation (100–120 dGA) on development of fetal HPAA function. We compared the effects of endogenous cortisol with synthetic glucocorticoid (GC) exposure, as used clinically to enhance fetal lung maturation. Pregnant sheep were exposed to repeated isolation stress twice per week for 3 h in a separate box with no visual, tactile, or auditory contact with their flock-mates either during early (n = 7) or late (n = 7) gestation. Additional groups received two courses of betamethasone (BM; n = 7; 2 × 110 μg kg− 1 body weight, 24 h apart) during late gestation (106/107 and 112/113 dGA, n = 7) or acted as controls (n = 7). Fetal cortisol responses to hypotensive challenge, a physiological fetal stressor, were measured at 112 and 129 dGA, i.e. before and during maturation of the HPAA. Hypotension was induced by fetal infusion of sodium nitroprusside, a potent vasodilator. At 112 dGA, neither PMS nor BM altered fetal cortisol responses. PMS, during early or late gestation, and BM treatment increased fetal cortisol responses at 129 dGA with the greatest increase achieved in stressed early pregnant sheep. Thus, development of the HPAA is vulnerable to inappropriate levels of GCs during long periods of fetal life, whereas early gestation is most vulnerable to PMS.